Environmental satisfaction levels of the elderly individuals in nursing home gardens - Eren, Emine Tarakci; Dzenli, Tugba; Var, Mustafa (SAGE PUBLICATIONS LTD, 2021)
The present study presents a three-step methodology to determine the environmental satisfaction levels of the elderly individuals in nursing home gardens. The first step comprised the selection of seven nursing homes in five provinces in the Eastern Black Sea region in Turkey. In the second step, 130 participants were selected among the residents of these seven nursing homes via random sampling. In the third step, the satisfaction level of the nursing home residents with the institution gardens was determined. A correlation analysis showed a positive relationship between the environmental and individual characteristics (r = 0.554; p < 0.01). Simple regression analysis was conducted to determine the effect of environmental characteristics on the satisfaction of individual needs, after determining the direction and level of the relationship between the environmental and the individual characteristics via correlation analysis. The analysis indicated a significant relationship between the environmental and individual characteristics (R = 0.610; R-2 = 0.373; F = 75.991; p <0.001). In conclusion, increased level of satisfaction with the existing physical characteristics of the gardens resulted in an increased level in meeting the psychosocial needs of the elderly individuals, thus, the environmental satisfaction level of nursing home residents increased as well.
Keywords: Elderly individuals; environmental satisfaction; nursing home gardens; physical properties; psychosocial needs; Turkey; INDOOR ENVIRONMENT; HEALTH OUTCOMES; CARE; RESIDENTS; CONTEXT; SPACES; PLACE; LIFE; Construction & Building Technology; Engineering; Public, Environmental & Occupational Health